Uterine artery hemodynamics in female dogs with open- and closed-cervix pyometra (Research, Society and Development, 2021)
Although pyometra is a common disease, the mechanisms that determine cervical opening remain unknown. Knowing that the vascular structures are crucial in pathophysiology, it was observed need for hemodynamic studies assessing uterine artery of female dogs with pyometra and its relation to the neck opening. Thirty-five female dogs were selected and separate into three groups: control group (CG) (n = 12), open-cervix pyometra group (OCG) (n = 11) and closed-cervix pyometra group (CCG) (n = 12), with the objective of evaluating and comparing the hemodynamic changes of the uterine artery [peak systolic velocity (PSV), end diastolic velocity (EDV), and resistance index (RI)] in female dogs with open- and closed-cervix pyometra and correlate them with measurements of uterine diameter (UD) and endometrial thickness (ET). The correlation analysis showed that, with the exception of PSV, the hemodynamics indices were associated with UD and ET, presenting a moderate and positive correlation between UD and EDV (r = 0.62; P